Using In-Row Pollenizers for Seedless Watermelon Production - J. H. Freeman; Steve M. Olson (EDIS)
HS-1079, a 3-page fact sheet by J.H. Freeman and S.M. Olson, describes the use of this strategy for increasing seedless watermelon yield, and the results of research comparing the effective of seven in-row pollenizer cultivars. Includes tables with characteristics of commercially available pollenizer cultivars, and plant population and plant cost analysis. Includes references. Published by the UF Department of Horticultural Sciences, January 2007.